Assessment of Malaria Parasite Intensity in Mono-Infected and Typhoid Co-Infected Patients Attending Selected Health Facilities in Wukari, Taraba State - John-Zakka U. E; Agere H. I. J; Amos T. J; Ogunmola A.O; Abdulrasheed M. H; Yafriyau E. P (Kwaghe International Journal of Sciences and Technology, 2026)
This study compared malaria parasite intensity in mono-infection and in co-infection with typhoid among febrile patients attending selected health facilities in Wukari. A total of 418 patients were enrolled based on clinical diagnosis of febrile illness, and from each patient blood and stool samples were collected for blood film examination and stool culture, respectively. Overall, 75.3% of malaria-positive cases had low parasite intensity, whereas 24.7% had higher parasite density, with a statistically significant difference (p < 0.001). Among the 83 patients with malaria mono-infection, low-intensity (+) parasitemia was more frequent than high-intensity parasitemia. By contrast, in malaria–typhoid co-infection, 68.9% of patients with Salmonella co-infection had high malaria parasite intensity and 31.1% had low intensity, with an overall p value < 0.011. The odds ratio of 6.766 indicates that individuals with high malaria intensity have approximately sevenfold higher odds of developing typhoid fever compared with those with low malaria intensity. These results suggest that elevated malaria parasite density in co-infected patients is associated with a greater risk of typhoid and indicate that healthcare providers should maintain heightened vigilance for severe malaria presentations in patients with concurrent typhoid infection. The findings further underscore the need for comprehensive control programs targeting mosquito breeding sites and public education on improved sanitation to reduce the burden of malaria and typhoid co-infection.